Reactions to territorial infringement - Brown, Graham; Robinson, S. (2011)
Territoriality represents a new area of research in organizations. In this study, we empirically examined how territorial infringement leads to anger and reactionary defenses. Using a cognitive appraisal theory of anger, we posited that a perceived infringement evokes anger that, in turn, fuels reactionary defenses. We tested our hypotheses by using data collected in an open-ended survey of 125 employees. They provided us with critical incidents of perceived infringement at work, which we then coded into quantitative measures. We found that employees are territorial over a wide variety of things at work, and they react in many ways when they perceive infringement of these territories. We discuss these findings and suggest several directions for future research in this emerging area. © 2011 INFORMS.